INFLUENCE OF REPEATED EARTHQUAKES ON THE DUCTILITY DEMAND OF INELASTIC RC BUILDINGS - Ade Faisal (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Current design practice considers the use of single event of earthquake. In fact seismic hazard is a multi events earthquake of the so-called repeated earthquakes. Consequently, the structural behaviour under repeated earthquakes is not clearly understood.